Adaptation of the Compensatory Stepping Response Following Predictable and Unpredictable Perturbation Training - Hasegawa, Naoya; Tanaka, Shintaro; Mani, Hiroki; Inoue, Takahiro; Wang, Yun; Watanabe, Kazuhiko; Asaka, Tadayoshi (Frontiers in Human Neuroscience, 2021)
Background: Effective training of the backward step response could be beneficial to improve postural stability and prevent falls. Unpredicted perturbation-based balance training (PBT), widely known as compensatory-step training, may enhance the fear of falling and the patterns of postural muscle co-contraction. Contrastingly, PBT with predictable direction or both direction and timing would suppress the fear and the co-contraction patterns during training, but the efficacy of predictable PBT for unpredictable perturbations is still unknown. Objective: To compare the adaptation effects of compensatory-step training with and without predictable perturbations on backward stepping against unpredictable perturbations. Methods: Thirty-three healthy young adults were randomly assigned to one of the following step training groups: Unpredicted, Predicted, and Self-initiated. In training sessions, participants were perturbed to induce a compensatory step with (Predicted group) or without (Unpredicted group) knowledge of the perturbation’s direction or while knowing both the direction and timing of the perturbation (Self-initiated group). In test sessions (pre- and post-training), participants were instructed to recover their postural stability in response to an unpredicted perturbation. The margin of stability (MOS), center of mass (COM), and step characteristics were measured during a backward step in both test and training sessions. Results: All three groups showed a significant increase in the step length and velocity in the post-training sessions compared to those in the pre-training sessions. Moreover, in the Unpredicted and Predicted groups, but not in the Self-initiated group, the MOS at step contact was significantly increased following the training session. In addition, the Self-initiated group showed a significant increase in COM shift at 50 ms after slip onset during training compared to the Unpredicted and Predicted groups. Conclusions: Unpredicted and predicted PBT improve step characteristics during backward stepping against unpredictable perturbations. Moreover, the unpredictable PBT and PBT with direction-predictable perturbations enhance the feedback postural control reflected as the postural stability at step contact. Contrastingly, PBT with direction- and timing-predictable perturbations may enhance feedforward postural control.